Study of age-related changes in plasma metabolites and enzyme activity of healthy small dogs that underwent medical checkups - Kusaba, Akio; Tago, Erika; Kusaba, Haruna; Kawasumi, Koh (Frontiers in Veterinary Science, 2024)
IntroductionIn Japan, the importance of medical checkups for pet dogs is increasing. In this study, we retrospectively explored the effects of age on plasma biomarkers in healthy small dogs that underwent medical checkups.MethodsBased on the modified American Animal Hospital Association Canine Life Stage Guidelines, 52 healthy small dogs were divided into 3 groups according to their life stage: young adult (1–4 years old), mature adult (5–11 years old), senior (12–15 years old). None of the dogs were obese. Plasma was collected from animals that underwent medical checkups at Muromi Animal Hospital (Fukuoka, Japan). Plasma glucose, triglyceride (TG), total protein, blood urea nitrogen (BUN), creatinine, total cholesterol, and albumin concentrations; alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase (ALP) activities; c-reactive protein (CRP), non-esterified fatty acid, malondialdehyde (MDA), serum amyloid A (SAA), insulin, and adiponectin (ADN) concentrations; glutathione peroxidase (GPx), superoxide dismutase (SOD), malate dehydrogenase (MDH), and lactate dehydrogenase (LDH) activities; and M/L ratio (MDH/LDH) were examined. Changes in the abovementioned plasma biomarker levels were compared between canines in different life stages.ResultsPlasma ADN concentrations and GPx, SOD, and MDH activities significantly decreased with age, whereas plasma ALP, BUN, TG, and MDA concentrations gradually increased. Plasma SAA levels measured by the latex agglutination method in 51 of the 52 small dogs that underwent medical checkups were below the detection limit.ConclusionPlasma ADN concentrations, GPx, SOD activity, and BUN levels may be important biomarkers for clarifying the effect of age in healthy dogs that undergo medical checkups. However, plasma SAA values obtained by the latex agglutination method were not considered an age-related inflammation marker for healthy dogs.